2013
DOI: 10.1002/pro.2237
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the sporulation phosphorelay: Crystal structure of the sensor domain of Bacillus subtilis histidine kinase, KinD

Abstract: The Bacillus subtilis KinD signal-transducing histidine kinase is a part of the sporulation phosphorelay known to regulate important developmental decisions such as sporulation and biofilm formation. We have determined crystal structures of the extracytoplasmic sensing domain of KinD, which was copurified and crystallized with a pyruvate ligand. The structure of a ligandbinding site mutant was also determined; it was copurified and crystallized with an acetate ligand. The structure of the KinD extracytoplasmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 52 publications
(71 reference statements)
2
48
0
1
Order By: Relevance
“…Previous studies have suggested that the sensor domain of KinD has an extra ligand between the ␣-helix and ␤-strands, and the ligand binding site may accommodate small molecules related to metabolism such as pyruvate or propionate (48). In the electron density map of Tll0287, we indeed found an extra density at the similar position between the ␣-helix and ␤-strands (Fig.…”
Section: Sequence and Structure Similaritysupporting
confidence: 64%
See 2 more Smart Citations
“…Previous studies have suggested that the sensor domain of KinD has an extra ligand between the ␣-helix and ␤-strands, and the ligand binding site may accommodate small molecules related to metabolism such as pyruvate or propionate (48). In the electron density map of Tll0287, we indeed found an extra density at the similar position between the ␣-helix and ␤-strands (Fig.…”
Section: Sequence and Structure Similaritysupporting
confidence: 64%
“…The results (supplemental Table S1) showed that the structure of Tll0287 is similar to that of a sensor domain contained in some kinases or sensor proteins possibly involved in cellular signal transduction, such as the sporulation kinase d domain from Bacillus subtilis (KinD, PDB code 4JGO) (48) (Fig. 6b) and a methyl-accepting chemotaxis protein (Mcp, PDB code 3C8C) (Fig.…”
Section: Sequence and Structure Similaritymentioning
confidence: 91%
See 1 more Smart Citation
“…The impact of signal molecule binding on the structure and stability of the SD has been rarely studied (23). To produce a conformational change, the binding of a signal molecule may induce the formation of an energetically favorable SD dimer or stabilize a weak SD dimer.…”
Section: Resultsmentioning
confidence: 99%
“…A PASlike (16) or "PDC" fold (17) is represented by the structures of PhoQ (17,18), DcuS (19), and CitA (16). The double PAS-like domain has also been observed in LuxQ (20), DctB (21,22), and in recently reported KinD (23). PAS-like SDs are believed to serve as ligand recognition units in extracytoplasmic signal transduction proteins (24).…”
mentioning
confidence: 98%